O papel do professor regente na formação de graduandos em situação de estágio de docência - LUZ, Rodrigo Santana da (2020)
This work has as its theme the training of future teachers and the curricular internship that constitute the focus of great political and educational debates in Brazil. In addition, it is important because during the internship it is the teacher regent who makes practical experience meaningful in that it facilitates the establishment of a link between academic knowledge and teaching practice. The importance of the study is based on the relevance of the contact of the future teacher, who happens during the internship, with the teachers in charge, since they are in the classroom, whose practice is the elaboration and application of practices in a context in which That there are complexities and confrontations of school reality. The study methodology was developed based on bibliographical research and data collection in books, articles, publications in scientific journals and dissertations. We have learned from this study that the supervised internship is of paramount importance for teacher training and that the performance of the regent teacher is essential for the development of the skills necessary for teaching functions.